Pengaruh Paparan Mikroplastik terhadap Stres Oksidatif dan Kinerja Pertumbuhan pada Ikan Nila (Oreochromis niloticus) - Andi Sudradjat; Rizky Pramono (Insight of Biology, 2026)
Microplastic pollution in aquatic environments has increased significantly and poses a threat to the health of cultured fish, including Nile tilapia (Oreochromis niloticus). This study aims to analyze the effects of microplastic exposure on oxidative stress and growth performance in Nile tilapia. The study applies an experimental approach based on the synthesis of empirical data from recent studies that evaluate physiological, biochemical, and growth responses of fish to microplastic exposure. The results indicate that microplastics induce the production of reactive oxygen species, leading to the activation of antioxidant defense systems and an increase in oxidative stress indicators. This condition is followed by a significant decline in specific growth rate, feed utilization efficiency, and fish survival rate. Long-term exposure also contributes to tissue damage and impaired organ function. These findings confirm that microplastics act as an environmental stressor that directly disrupts physiological balance and production performance in Nile tilapia. This study provides a scientific basis for more adaptive aquaculture environmental management in response to microplastic contamination risks.